Pleural Effusion Associated with Ulcerative Colitis: A Case Report - Al Ashkar, Rana; Nasser El Dine, Rabab; Harb, Rachad; AlMoussawi, Mohamed; Soukarieh , Khaled (International Journal of Clinical Research, 2024)
Background: Extraintestinal manifestations associated with IBD may involve the skin, joints, hepatobiliary tract, eye, kidney, and rarely pancreas and respiratory systems; as well as risks for venous thrombosis. They may be present at diagnosis or develop later in the disease course. Pulmonary complications of IBD include airway inflammation, parenchymal lung disease, serositis, thromboembolic disease, and drug-induced lung toxicity. Case Presentation: We report a case of a 41-year-old lady with ulcerative colitis who presented to the hospital with respiratory symptoms. Physical examination and imagery lead to the diagnosis of acute pleural effusion. Later on, the patient developed gastrointestinal symptoms. Colonoscopy and biopsy showed that she has Ulcerative Colitis. Which is a very rare presentation of EIM of IBD. The patient improved on steroids and mesalamine and pleural effusion resolved. Conclusion: In conclusion, pulmonary involvement should be considered when pleurisy develops in UC. Early diagnosis and effective treatment are important for these patients.